Influence of nicotine and cotinine impregnation on the first step of periodontal regeneration: clot stabilization - Pinto, Shelon Cristina Souza; Leite, Fabio Renato Manzolli; Fontanari, Lucas Amaral; Cavassim, Rodrigo; Leite, Amauri Antiqueira; Bandéca, Mateus Coelho; Borges, Alvaro Henrique; Sampaio, Jose Eduardo Cezar [UNESP] (My University, 2013)
This study analyzes the clot stabilization on root surfaces of teeth impregnated with cotinine and nicotine and the influence of the scaling in the adhesion of blood components, observing the influence of new exposition to nicotine and/or cotinine after scaling. Fifteen human teeth extracted due to periodontal disease of non-smokers patients were selected and manually scaled. Four dentin blocks were obtained from each tooth (n = 60). Samples received blood application or reimpregnation with nicotine and/or cotinine, depending on the groups. Group 1: PBS immersion + root scaling + blood; group 2: nicotine + root scaling + blood; group 3: nicotine + root scaling + nicotine reapplication + blood; group 4: cotinine + root scaling + blood; group 5: cotinine + root scaling + cotinine reapplication+ blood; group 6: nicotine and cotinine + root scaling + nicotine and cotinine + blood. Samples were kept in 2 ml of each substance for 24 hours. Each group received a blood drop and was analyzed by SEM. The higher amount of blood components was present in teeth exposed to cotinine and the groups submitted to scaling and blood application in comparison with groups that received reapplication of toxic substances after scaling. The greater toxic effect on root dentin surface was after the exposure to nicotine and cotinine. Results suggest that periodontal healing may be delayed in smokers due to the direct inhibition of clot stabilization on the root surface when nicotine and cotinine are present concomitantly.
Keywords: Clot stabilization; Periodontal regeneration; Nicotine; Cotinine